Pannenberg's Critique of Barth's Theology of the Word - VanderPlaat, Hilbert (My University, 1983)
This thesis deals with what two modern theologians have said about knowledge of God. Karl Barth, who must be regarded as the most influential theologian of this century, defended the position that God can only be known through his revelation in Christ - the Word of God. Consequently, any attempt on man's part to attain to knowledge of God in another way must be seen as an expression of his refusal to recognize the freedom and grace of God. Theology, according to Barth, is only true to its calling if it submits to the Word and accepts it unquestioningly as the point of departure for theological reflection. Wolfhart Pannenberg belongs to the post-Barthian era. He is deeply concerned about the situation in which theology finds itself today. It is his firm conviction that a 'Theology of the Word' leads the Church into a ghetto and fails tzo respond to the challenge of atheism. Pannenberg observes that the word 'God' has become a meaningless sound to many of our contemporaries, which is precisely the reason why theology ought to render a reasonable or rational account of the Christian faith. Theology must engage in such a task not only for the sake of those who have become estranged from the Christian tradition, but also and equally for people who confess Jesus Christ as Savior and Lord. Christians, too, need the assurance that their faith is not based on private experiences or subjective decisions, otherwise they will not be able to free themselves from the gnawing doubt that their faith might be an illusion, a merely subjective affair without a corresponding reality. Pannenberg presents us with a program of which many details still have to be worked out. Nevertheless, his numerous publications give us a clear picture of the direction theology is to take. The main elements in his approach are (1) the development of a philosophical theology with a basis in modern anthropology, and (2) the development of a concept of revelation as history; i.e., revelation is not so much a matter of divine words as of historical acts which can be verified by means of the historical-critical method. It is the contention of this author that there are indeed differences between Barth and Pannenberg but they are not nearly so radical as the latter contends.
Keywords: Religion; Religion